Helicobacter pylori Infection in Ontario: Prevalence and Risk Factors. (2007) - Naja, Farah; Kreiger, Nancy; Sullivan, Terrence
Abstract : BACKGROUND: Helicobacter pylori has been classified by the World Health Organization as a type I carcinogen. Nearly 50% of the world's population is estimated to be infected with H pylori . Prevalence patterns of the infection are different between developing and developed countries. The present study had two objectives – to estimate the prevalence of H pylori infection in Ontario, and to evaluate the relationship between the infection and various demographic characteristics and selected lifestyle factors. METHODS: Ten microlitres of plasma were aliquoted from stored blood of 1306 men and women, 50 to 80 years of age, from Ontario. The blood samples belonged to control patients of a colorectal cancer population-based study group. Serological testing was used to detect H pylori infection; information was obtained on dietary intake and lifestyle habits, as well as past and present medical history, education, income, number of siblings, ethnicity and place of birth. RESULTS: The overall weighted seroprevalence of H pylori was 23.1% (95% CI 17.7% to 29.5%), with men having higher infection rates (29.4%, 95% CI 21.1% to 39.3%) than women (14.9%, 95% CI 10.1% to 21.4%). Seroprevalence of the infection increased significantly with age and number of siblings. Increased risk was also associated with being nonwhite, being born outside of Canada and immigrating at 20 years of age or older. An inverse association with seroprevalence was found for education and alcohol consumption. CONCLUSION: The prevalence of H pylori infection in Ontario is comparable with that of other developed countries. Age, sex, number of siblings, ethnicity, place of birth and age at immigration are among the factors associated with H pylori infection.